Parking Garage Measurements Indicating a Gamma Spectrometer-Neutron Counter Background Correlation - Jackson N Wagner; Craig Marianno; Thomas McCullough (International Journal of Nuclear Security, 2020)
Gamma spectroscopy and gross neutron counting systems are commonly employed together during nuclear security operations, particularly mobile searches. The data from these systems are typically analyzed independently; however, operational data suggest a relationship between the background signals from both systems. This relationship appears to occur between the neutron count rate and the high energy (greater than 3 MeV) gamma spectrometer count rate for background conditions. To verify the presence of this correlation, high energy gamma ray and neutron count rates were measured in five parking garages on the Texas A&M University campus. These measurements employed one 4” x 4” x 16” NaI detector with an Ortec digiBASE MCA, four moderated 1” x 18” 3He tubes (part of the Ortec NAI-SS system), and two unmoderated 2” x 15” 3He tubes (part of a Thermo PackEye system). The NaI detector was calibrated to a 50 MeV scale and ignored signals less than 4 MeV. Results show a decrease in the count rate of each detector as the systems were moved further below the roof of each garage. These decreases appear linear, but exponential relationships are plausible. More importantly, the data also show that the count rates from the two different detector types are linearly related. The linear relationships are strong, and the slopes vary depending on which neutron counter is considered against the gamma spectrometer. While it is possible that these relationships are the result of the NaI system detecting 4-50 MeV (or even higher energy) gamma rays, it is more likely that this system is detecting charged particles: muons generated by cosmic ray interactions with the atmosphere or protons produced by the decay of free neutrons. All three of these particles would be produced proportionally to the neutrons that the 3He tubes would detect, either from the decay of the neutrons themselves or by being produced from the same cosmic ray interactions that produce the neutrons.
Keywords: mobile search; background; NaI; neutron counting